2020
DOI: 10.23950/1812-2892-jcmk-00733
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lactate level and length of hospital stay in patients with a COPD exacerbation

Abstract: Objective: To investigate the effect of lactate levels on length of hospital stay in patients with chronic obstructive pulmonary disease exacerbation.Material and methods: Patients who were hospitalized for chronic obstructive pulmonary disease exacerbation between October 2017 and December 2018 were evaluated. Those who had pneumonia or any other additional disease that might affect the lactate level during hospitalization were excluded from the study. The arterial blood gas parameters and lactate levels meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although a single lactate measurement at the time of admission was used in our study, studies in the literature showed that lactate levels measured at 1-2 hour intervals give more effective results in critically ill patients [20,21]. In addition, there are studies reporting a positive relationship between lactate levels and length of hospital stay in patients with COPD exacerbations, and a positive relationship between lactate clearance and ED outcome in these patients [22,23]. In our study, patients were compared in two groups as those who were with and without hyperlactatemia (lactate>2 mmol/L) according to their lactate values at the time of ED admission.…”
Section: Discussionmentioning
confidence: 99%
“…Although a single lactate measurement at the time of admission was used in our study, studies in the literature showed that lactate levels measured at 1-2 hour intervals give more effective results in critically ill patients [20,21]. In addition, there are studies reporting a positive relationship between lactate levels and length of hospital stay in patients with COPD exacerbations, and a positive relationship between lactate clearance and ED outcome in these patients [22,23]. In our study, patients were compared in two groups as those who were with and without hyperlactatemia (lactate>2 mmol/L) according to their lactate values at the time of ED admission.…”
Section: Discussionmentioning
confidence: 99%
“…In critical care, refractory shock (40%) and comorbid withdrawal of care (44%) were the most common reasons for death in patients with sepsis and septic shock [10]. Initial serum lactate level was associated with longer duration of hospitalization in patients with COPD exacerbation; serum lactate clearance also showed lower both in-hospital and long-term survival in critically ill patients in the ICU [11,12]. According to our study results, the presence of shock and high serum lactate may be a good predictor of mortality in patients with severely exacerbated COPD with acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…In critical care, refractory shock (40%) and comorbid withdrawal of care (44%) were the most common reasons for death in patients with sepsis and septic shock [11]. Initial serum lactate level was associated with longer duration of hospitalization in patients with COPD exacerbation; serum lactate clearance also showed lower both in-hospital and long-term survival in critically ill patients in the ICU [12,13]. According to our study results, the presence of shock and high serum lactate may be a good predictor of mortality in patients with severely exacerbated COPD with acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%